Pengendalian Kasus Berat Badan Lahir Rendah (BBLR) Dengan Pendekatan Asset Based Community Development (ABCD) Di Puskesmas Tamangapa Kota Makassar - Alamsyah Rajab, Muhammad Nur; Haruna, Nadyah; Rahim, Rosdianah; Darmawansyih; Sewang, Ahmad (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
Low Birth Weight (LBW) is a birth weight of less than 2500 grams. Birth weight is an indicator of a child's growthand development into adulthood and describes the nutritional status of the fetus during the womb. The Asset BasedCommunity Development (ABCD) approach owned by the community is to obtain a common goal in controlling LBWstarting from asset identification, problem analysis, potential planning, implementation, and utilization. The focus ofthe research conducted by the author is the identification of human resources (HR) assets towards controlling casesof Low Birth Weight (LBW). This type of research is qualitative research with an Asset Based Community Development(ABCD) approach with observation and In Depth Interview methods. The method of taking informants is snowballsampling in the Tamangapa Health Center working area in 2022. The results showed that controlling cases of lowbirth weight (LBW) with the Asset Based Community Development (ABCD) method at Puskesmas Tamangapa isHuman Assets, namely Health services (pregnant women's programs such as ANC visits, pregnant women's classes,posyandu cadres, whatsapp groups for pregnant women to fulfill nutrition during pregnancy, fulfillment of additionalfood (PMT), neonatal visits, and kangaroo method care), education and knowledge of pregnant women. Economicassets depend on the profession of each resident such as self-employed and civil servants, farmers, breeders, traders.These four assets are very supportive in efforts to control low birth weight cases (LBW) in the Tamangapa HealthCenter working area.